Modern Habsburg population censuses in Cislajtania and their abuses in the Austrian-Illyrian Primorje from the perspective of preserved census sheets (notes and notices) - Ivica Pletikosić (Journal for Geography, 2024)
The statistical literature, which contains data for the period of the Habsburg modern population censuses, was created on the basis of calculations by municipal officials. Only they leafed through the notes and notices and sent the calculated data to Vienna for printing by the state printing house. Re-examining these sources offers a whole new perspective on the censuses in question. The purpose of the article is to present the biggest differences between the established truths and the view from this new angle.